Sedimentology and architecture of sharp-based tidal sandstones in the upper Marambio Group, Maastrichtian of Antarctica - Olivero, Eduardo Bernardo (2008)
At Snow Hill and Seymour islands, northeastern Antarctic Peninsula, the early Maastrichtian part of the Marambio Group consists in ascending stratigraphic order of a) fossiliferous mudstone and sandstone of the Snow Hill Island Formation (> 140 m thick), b) glauconitic beds of the Haslum Crag Sandstone (ca. 200 m thick), and c) the mudstone-rich basal López de Bertodano Formation (ca. 400 m thick). The study of fourteen sedimentary sections located along the depositional strike reveals complex arrangements of facies associations and stratal architecture for these units. The Snow Hill Island Formation consists of coarsening and thickening upward successions, 3–7 m thick, of interbedded mudstone and sandstone recording prograding deltaic lobes. Above a marked unconformity, the Haslum Crag Sandstone, bioturbated glauconitic sandstone and mudstone with inclined heterolithic stratification, records the incision, migration, and filling of relatively large and deep subtidal channels. Deeply incised into the Haslum Crag Sandstone, the López de Bertodano Formation includes transgressive estuarine and shallow marine deposits that fill a previous fluvially and/or tidally scoured depression. The Haslum Crag Sandstone consists of forced regressive deposits formed during relative sea-level falls, and documents a rare case of sharp-based, tide-influenced sandstone encased in marine and estuarine mudstone. The main differences between the Haslum Crag Sandstone and other forced regressive, wave-influenced sharp-based sandstones are twofold: a) it records basal erosion by tidal processes — an erosional feature not as yet fully documented in forced regressions, and b) it records a rare case of tide-influenced deposits originating during overall regressive conditions. The great thicknesses of tide-influenced forced regressive deposits (Haslum Crag Sandstone) and the transgressive, estuarine deposits (López de Bertodano Formation) suggest the occurrence of several high-frequency sea-level changes, probably driven by tectonic processes.